PERCEPTIONS OF VETERINARIANS IN RELATION TO FELINE POSSESSION IN BUENOS AIRES CITY, ARGENTINA - Degregorio J., Osvaldo (2009)
The objective of the present study was to determine the perceptions of veterinarians in relation to motivations, attitudes, and behaviour of people that owns or does not owns felines. Veterinarians (n = 62) from Buenos Aires city, Argentina, working in the clinic and surgery of pets were surveyed. Variables were evaluated by the analysis of content and index position. The main reasons to own felines were preference and family customs. The most frequent way of getting a feline was as a gift, collected from public areas or purchased. Veterinarians indicated that most of these animals have an intimate relationship with the owner, as well as low anxiety and aggressiveness. Feline behaviour cognitive maps were developed pointing out its relationship with owners’ attitudes and behaviours.